Professional development of social work in Russia - Elena Iarskaia-Smirnova (Social Work and Society)
The aim of the paper was to get an understanding about how the profession of social work explains its relevance and legitimacy in today's Russia, to enlighten the importance of socio-political, professional and educational contexts in explaining the societal position of the social work profession in Russia. This paper begins with the analysis of the processes of legitimization, professionalization and constitution of social work in today's Russia. In addition to functionalist and critical perspectives on these three processes, in its second part the paper employs phenomenological approach looking into everyday life theory of social work that is constructed in routine work at the social service agencies. The third part of this paper talks about the issues of social services and social work with family and children in contemporary Russia.